2004
DOI: 10.1002/ccd.10685
|View full text |Cite
|
Sign up to set email alerts
|

Transradial application of percusurge guardwire device during primary percutaneous intervention of infarct‐related artery with high‐burden thrombus formation

Abstract: A large infarct-related artery (IRA), which mostly contains high-burden thrombus formation (HBTF) and lipid pool-like plaque contents, has been suggested to play a pivotal role in the no-reflow phenomenon during primary percutaneous coronary intervention (p-PCI). To reduce the thrombus burden of the IRA using the PercuSurge GuardWire device before intervention may be of crucial importance to preventing no-reflow. The purposes of this study were to test the transradial application (TRA) of this new mechanical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…According to previous reports 36,37 that revealed the distal protection device to be effective in acute MI, distal embolism of thrombus was suggested as a major cause of microcirculation damage. However, the pathological examination of the aspirated samples in the present study revealed that samples from the patients with ruptured plaque contained more plaque debris than those without ruptured plaque.…”
Section: Distal Embolism Of Plaque Debris May Be the Major Cause Of Mmentioning
confidence: 99%
“…According to previous reports 36,37 that revealed the distal protection device to be effective in acute MI, distal embolism of thrombus was suggested as a major cause of microcirculation damage. However, the pathological examination of the aspirated samples in the present study revealed that samples from the patients with ruptured plaque contained more plaque debris than those without ruptured plaque.…”
Section: Distal Embolism Of Plaque Debris May Be the Major Cause Of Mmentioning
confidence: 99%
“…The procedures and protocol were described previously [11]. Briefly, a transradial artery approach using 6 Fr arterial sheath is the design protocol for AMI in our hospital unless Allen's test is positive.…”
Section: Procedures and Protocolmentioning
confidence: 99%
“…Recently, we reported preliminary data on utilization of the PercuSurge device during primary PCI [11]. Most of our patients have now received a 6-month angiographic follow-up.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations